Cross-species recognition of two porcine coronaviruses to their cellular receptor aminopeptidase N of dogs and seven other species. - Yuyang Tian; Junqing Sun; Xiaohan Hou; Zhimin Liu; Zeao Chen; Xiaoqian Pan; Ying Wang; Jianle Ren; Ding Zhang; Bo Yang; Longlong Si; Yuhai Bi; et al. (PLoS Pathogens)
Porcine deltacoronavirus (PDCoV) and transmissible gastroenteritis coronavirus (TGEV), the two causative agents of porcine diarrhea, have been reported to be at risk of cross-species transmission, including to humans. However, the potential host range in which these two CoVs interact remains unclear. We screened 16 animal counterparts for porcine aminopeptidase N (APN), the receptor of PDCoV and TGEV, and found that APNs from eight of 17 animals could bind to the receptor-binding domains (RBDs) of PDCoV and TGEV. Furthermore, the animal APNs that could bind to the RBDs could mediate cellular infection by both viruses. Dog APN (dAPN) has been identified as the animal receptor with the highest capability to mediate the virus infection. We further resolved the complex structures of dAPN bound to the PDCoV RBD/TGEV RBD, respectively, establishing its divergent receptor-binding modes. We identified R325 of dAPN as an important residue in the PDCoV RBD-dAPN interaction, and found the central role of Q746 and T749 in dAPN in the interaction with the TGEV RBD. These findings provide the molecular basis of the potential cross-species transmission of these two porcine CoVs and shed light on future surveillance of these CoVs.